Calcium dynamics and modulation in carrot somatic embryogenesis - Calabuig-Serna, Antonio; Mir, Ricardo; Arjona, Paloma; Seguí-Simarro, Jose María (Frontiers in Plant Science, 2023)
Free calcium (Ca+2) is a pivotal player in different in vivo and in vitro morphogenic processes. In the induction of somatic embryogenesis, its role has been demonstrated in different species. In carrot, however, this role has been more controversial. In this work, we developed carrot lines expressing cameleon Ca+2 sensors. With them, Ca+2 levels and distribution in the different embryogenic structures formed during the induction and development of somatic embryos were analyzed by FRET. We also used different chemicals to modulate intracellular Ca+2 levels (CaCl2, ionophore A23187, EGTA), to inhibit calmodulin (W-7) and to inhibit callose synthesis (2-deoxy-D-glucose) at different times, principally during the first stages of embryo induction. Our results showed that high Ca+2 levels and the development of a callose layer are markers of cells induced to embryogenesis, which are the precursors of somatic embryos. Disorganized calli and embryogenic masses have different Ca+2 patterns associated to their embryogenic competence, with higher levels in embryogenic cells than in callus cells. The efficiency of somatic embryogenesis in carrot can be effectively modulated by allowing, within a range, more Ca+2 to enter the cell to act as a second messenger to trigger embryogenesis induction. Once induced, Ca+2-calmodulin signaling seems related with the transcriptional remodeling needed for embryo progression, and alterations of Ca+2 or calmodulin levels negatively affect the efficiency of the process.